The Impact of Skin Care Products on the Skin Health (Advancements in Homeopathic Research, 2022)
The skin is the largest organ of the body, with a total area of about 20 square feet and also the most exposed. The skin protects us from microbes and the elements, helps regulate body temperature, and permits the sensations of touch, heat, and cold.1The review evaluates the current scenario of cosmetic use and their damaging tendencies in different organs of human body. The continuous and homogenous exposure to chemicals present in cosmetic products is health deteriorating at an alarming rate. Various cosmetic products are full with number of raw ingredients such as surfactants, foam agents, fragrances, thickeners, minerals, metals, and preservatives have synthetic origin, and hence, pose a disturbance to normal physiology and are harmful for health, percutaneous absorption of irritants, and allergens of dermal skin.3
Keywords: Skin Care Products; Skin Health; surfactants; foam agents; fragrances; physiology